Improving comfort in clothing - Song, Guowen (Woodhead publishing in textiles ;, 2011)
Statistics show that the wear comfort is the most important property of clothing demanded by consumers. This book is the first of its kind to compile all the information on clothing comfort into one complete volume, providing the reader with a fundamental understanding of comfort and how to design textiles to maximise comfort for the wearer. Part 1 includes the fundamental principles of comfort. Part 2 reviews how to measure and assess comfort. Part 3 analyses how to improve the physical aspects of comfort in textiles and apparel and part 4 concludes with a range of case studies involving the incorporation of comfort, such as medical and sportswear applications.